Alterations in Yeast Species Composition of Uninoculated Wine Ferments by the Addition of Sulphur Dioxide - Kathleen Cuijvers; Steven Van Den Heuvel; Cristian Varela; Mark Rullo; Mark Solomon; Simon Schmidt; Anthony Borneman (Fermentation, 2020)
Uninoculated wine fermentations are conducted by a consortium of wine yeast and bacteria that establish themselves either from the grape surface or from the winery environment. Of the additives that are commonly used by winemakers, sulphur dioxide (SO2) represents the main antimicrobial preservative and its use can have drastic effects on the microbial composition of the fermentation. To investigate the effect of SO2 on the resident yeast community of uninoculated ferments, Chardonnay grape juice from 2018 and 2019 was treated with a variety of SO2 concentrations ranging up to 100 mg/L and was then allowed to undergo fermentation, with the yeast community structure being assessed via high-throughput meta-barcoding (phylotyping). While the addition of SO2 was shown to select against the presence of many species of non-Saccharomyces yeasts, there was a clear and increasing selection for the species Hanseniaspora osmophila as concentrations of SO2 rose above 40 mg/L in fermentations from both vintages. Chemical analysis of the wines resulting from these treatments showed significant increases in acetate esters, and specifically the desirable aroma compound 2-phenylethyl acetate, that accompanied the increase in abundance of H. osmophila. The ability to modulate the yeast community structure of an uninoculated ferment and the resulting chemical composition of the final wine, as demonstrated in this study, represents an important tool for winemakers to begin to be able to influence the organoleptic profile of uninoculated wines.